Successfully reported this slideshow.
We use your LinkedIn profile and activity data to personalize ads and to show you more relevant ads. You can change your ad preferences anytime.
Upcoming SlideShare
×

# Lesson 8: Derivatives of Logarithmic and Exponential Functions (worksheet solutions)

5,549 views

Published on

• Full Name
Comment goes here.

Are you sure you want to Yes No
Your message goes here
• Be the first to comment

### Lesson 8: Derivatives of Logarithmic and Exponential Functions (worksheet solutions)

1. 1. Solutions to Worksheet for Sections 3.1–3.3 Derivatives of Exponential and Logarithmic Functions V63.0121, Calculus I Summer 2010 Find the derivatives of the following functions. 2 −3x 1. y = e2x Solution. We have dy 2 d 2 = e2x −3x 2x2 − 3x = e2x −3x (4x − 3) dx dx 2. y = 62x Solution. We have y = (ln 6) · 62x · 2 = (2 ln 6)62x 3. y = ln(x3 + 9) Solution. We have dy 1 d 3x2 = 3 x3 + 9 = 3 dx x + 9 dx x +9 4. y = log3 ex Solution. By brute force we have 1 1 y = · ex = (ln 3) · ex ln 3 But slightly more elegantly, we notice that ln ex x log3 ex = = ln 3 ln 3 dy 1 So = makes a lot of sense. dx ln 3 1
2. 2. 5. y = log10 3θ2 −θ Solution. dy 1 2 −1/2 1 2 = log10 3θ −θ · θ 2 −θ · (ln 3) · 3θ −θ (2θ − 1) dx 2 (ln 10)3 ln 3 2θ − 1 = · 2 ln 10 log10 3θ2 −θ There’s some simpliﬁcations we could do before diﬀerentiation, however. 2 −θ ln 3θ θ2 − θ ln 3 ln 3 2 θ 2 −θ log10 3 = = = θ −θ ln 10 ln 10 ln 10 So ln 3 y= · θ2 − θ ln 10 ln 3 2θ − 1 y = · √ ln 10 2 θ2 − θ 6. y = sin2 x + 2sin x Solution. y = 2 sin x cos x + 2sin x · ln 2 · cos x Use logarithmic diﬀerentiation to ﬁnd the derivatives of the following functions. 7. y = x x2 − 1 Solution. We have 1 ln(x2 − 1) ln y = ln x + 2 1 dy 1 1 2x = + · 2 y dx x 2 x −1 dy 1 x = x x2 − 1 + 2 dx x x −1 8. y = (x − 1)(x − 2)(x − 3) 2
3. 3. Solution. We have 1 ln y = (ln(x − 1) + ln(x − 2) + ln(x − 3)) 2 1 dy 1 1 1 1 = + + y dx 2 x−1 x−2 x−3 dy 1 1 1 1 = (x − 1)(x − 2)(x − 3) + + dx 2 x−1 x−2 x−3 x(x − 1)3/2 9. y = √ x+1 Solution. We have 3 1 ln y = ln x +ln(x − 1) − ln(x + 1) 2 2 1 dy 1 3 1 1 1 = + · − · y dx x 2 x−1 2 x+1 dy x(x − 1)3/2 1 3 1 1 1 = √ + · − · dx x+1 x 2 x−1 2 x+1 3